Impact of normative brain volume reports on the diagnosis of neurodegenerative dementia disorders in neuroradiology: A real-world, clinical practice study - Hedderich, Dennis M.; Schmitz-Koep, Benita; Schuberth, Madeleine; Schultz, Vivian; Schlaeger, Sarah J.; Schinz, David; Rubbert, Christian; Caspers, Julian; Zimmer, Claus; Grimmer, Timo; Yakushev, Igor (Frontiers in Aging Neuroscience, 2022)
Background: Normative brain volume reports (NBVR) are becoming more available in the work-up of patients with suspected dementia disorders, potentially leveraging the value of structural MRI in clinical settings. The present study aims to investigate the impact of NBVRs on the diagnosis of neurodegenerative dementia disorders in real-world clinical practice. Methods: We retrospectively analyzed data of 112 memory clinic patients, who were consecutively referred for MRI and 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET) during a twelve-month period. Structural MRI was assessed by two residents with two and three years of neuroimaging experience. Statements and diagnostic confidence regarding the presence of a neurodegenerative disorder in general (first level) and Alzheimer's disease (AD) pattern in particular (second level) were recorded without and with NBVR information. FDG-PET served as reference standard. Results: Overall, despite a trend towards increased accuracy, the impact of NBVRs on diagnostic accuracy was low and non-significant. We found a significant drop of sensitivity (0.75 to 0.58; p<0.001) and increase of specificity (0.62 to 0.85; p<0.001) for rater 1 at identifying patients with neurodegenerative dementia disorders. Diagnostic confidence increased for rater 2 (p<0.001). Conclusions: Despite the limited impact on diagnostic accuracy, the specificity increase at identifying patients with neurodegenerative disorders might be important in clinical practice, since it was raised to a subspecialist level (>80%). Future efforts should aim at improving technical factors in order to narrow the gap between metabolic and structural imaging as well as on studying how NBVR information is being integrated into medical professional decision-making.